1979
DOI: 10.1042/bj1770721
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-induced inactivation of transminases by acetylenic and vinyl analogues of 4-aminobutyrate

Abstract: The reactions of two analogues of 4-aminobutyrate, namely 4-aminohex-5-ynoate and 4-aminohex-5-enoate, with three transaminases were studied. Three pure enzymes were used, aminobutyrate transaminase (EC 2.6.1.19), ornithine transaminase (EC 2.6.1.13) and aspartate transaminase (EC 2.6.1.1), and the course of the reactions was studied by observing changes in the absorption spectrum of the bound coenzyme and by observing loss of activity. All of the enzymes were inactivated by either inhibitor, but amino-hexenoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…It also inactivates aspartate aminotransferase. 53 We have found that 15 neither inactivates ( A ) nor inhibits ( B ) alanine aminotransferase and aspartate aminotransferase (data not shown) up to 6 mM concentration (Figure 5). 50 …”
Section: Introductionmentioning
confidence: 77%
“…It also inactivates aspartate aminotransferase. 53 We have found that 15 neither inactivates ( A ) nor inhibits ( B ) alanine aminotransferase and aspartate aminotransferase (data not shown) up to 6 mM concentration (Figure 5). 50 …”
Section: Introductionmentioning
confidence: 77%
“…A first result in this direction has been published recently (63). GEG (1), one of the first rationally designed mechanism-based inactivators, was shown to be a potent inactivator of GABA-AT (30,64,65). In vivo, GEG causes a long-lasting decrease in mouse brain GABA-AT activity in a dose-dependent manner when administered peripherally and has been shown to increase synaptosomal GABA levels (66,67).…”
Section: Discussionmentioning
confidence: 97%
“…The drug is sold as a racemic mixture, and it is not known how many of the side effects arise from the administration of the inactive enantiomer (R-isomer). Other mechanism-based inactivators of GABA-AT, such as gabaculine (30,31) and ethanolamine-O-sulfate (32), are generally toxic, nonspecific, and/or cross the blood-brain barrier poorly.…”
mentioning
confidence: 99%
“…However, since visual dysfunctions are also caused by other anticonvulsant drugs, this side effect may be a relatively common outcome of anticonvulsant treatment or even a feature of the natural history of epilepsy itself [61,62]. Other mechanism-based inhibitors, studied in the 1970s, such as gabaculine [63,64], resulted to be toxic, non-specific or poorly crossing the blood-brain barrier. Consequently, novel GABA-AT inhibitors are urgently required as therapeutic agents for epilepsy and other CNS pathologies.…”
Section: Branched-chain Amino Acid Aminotransferasementioning
confidence: 95%